OKSIDASI SORBITOL MENGGUNAKAN MOLEKUL OKSIGEN YANG DIAKTIFASI KATALIS Pd/-Al2O3 DALAM PELARUT AIR - Andriayani -; Saur Lumban Raja (Jurnal Riset Kimia, 2007)
ABSTRACT The sorbitol has been oxidized by molecular oxygen that activated by Pd/g-Al2O3 catalyst in water solvent at 70°C. The product was contained 1.3 g (26%) of the glucaric acid. The product was characterized by FT-IR and 1H-NMR spectrophotometer. The product oxidation was reacted with solution of sodium hydroxide methanol at 70°C during 5 hours produced sodium dicarboxylate in the form yellow gel about 0.3 g (30%). The product was characterized by FT-IR and 1H-NMR spectrophotometer. Keywords: sorbitol, oxidation, catalyst, Pd/g-Al2O3, oxygen molecular